Ecclesiastics and political state building in the Iberian monarchies, 13th-15th centuries - Hermínia Vasconcelos Vilar, Maria João Branco (dir.) (Publicações do Cidehus, 2016)
The project ""The European Dimension of a Group of Power: Ecclesiastics and the political State Building of the Iberian Monarchies (13th-15th centuries)" supported by the Fundação para a Ciência e Tecnologia assembled an inter-university team, that brought together researchers from five Portuguese universities and three Spanish universities, as well as consultants from three different universities. The book now being published is one of the outcomes of the work undertaken by the Iberian inte...